Behind the hyperbole CDC and SBMA after all these years - Yap, Virginia C. (2001)
Clark Special Economic Zone a9CSEZ) and Subi Bay Freeport Zone (SBFZ) were established to improve the livelihood of the people in Central Luzon in general and their host provinces in particular. This task was made even more urgent by the destruction wrought by Mr. Pinatubo in. 1991. Eleven years after the establishment of the two major special economic zones (SEZ's) in Central Luzon, a question may be posed: "What have been the contributions of the CSEZ and SBFZ to the economy of Central Luzon and to their host provinces?" This paper reveals that the data on the two SEZ's show the latter's considerable contributions to the economy of Central Luzon in terms of investment, employment and foreign exchange, with the contribution being the greatest in the latter. Bt data also show that investment contribution of employment figures have not been up to expectations. A number of attendant developmental issues and concerns have emerged from the establishment of the two SEZ's.
Keywords: Territorial waters